2011
DOI: 10.1179/030192310x12690127076316
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and enrichment of phosphorus in solidified BOF steelmaking slag

Abstract: The distribution of P in basic oxygen furnace steelmaking slag was investigated together with the enrichment behaviours of P in slowly cooled slag samples modified by SiO 2 from high temperature remelts at 1873 K. The slag microstructures were characterised, and the results showed that only a limited fraction of P 2 O 5 was dispersed in the matrix, whereas a large amount of P 2 O 5 was found to form solid solutions with dicalcium silicate (2CaO.SiO 2 or C 2 S) phase and/or with tricalcium silicate (3CaO.SiO 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 9 publications
0
34
0
Order By: Relevance
“…The generation reaction of nC 2 S-C 3 P solid solution in P bearing slag is as follows 2CaOzSiO 2~C a 2 SiO 4 (1) During slag cooling, Ca, Si and O are first precipitated as nCaO.SiO, Ca 2 SiO 4 and Ca 3 (PO 4 ) 2 phase can be dissolved with each other in any proportion. The enrichment effect depends on the generation of nC 2 S-C 3 P solid solution.…”
Section: Thermodynamic Analysis Of Sio 2 Modificationmentioning
confidence: 99%
“…The generation reaction of nC 2 S-C 3 P solid solution in P bearing slag is as follows 2CaOzSiO 2~C a 2 SiO 4 (1) During slag cooling, Ca, Si and O are first precipitated as nCaO.SiO, Ca 2 SiO 4 and Ca 3 (PO 4 ) 2 phase can be dissolved with each other in any proportion. The enrichment effect depends on the generation of nC 2 S-C 3 P solid solution.…”
Section: Thermodynamic Analysis Of Sio 2 Modificationmentioning
confidence: 99%
“…Given that the calcium ferroaluminates in the slag residue leached by ammonium chloride solution still contain relatively high contents of calcium, it shows that the calcium in the form of calcium ferroaluminates is difficult to extract. Moreover, as the phosphorus is mainly dissolved in C2S and C3S in the steelmaking slag [28,29], the leached slag residue particles containing phosphorus, probably the calcium silicates before leaching, have high levels of silicon and less amounts of iron and calcium, which indicates that most of the calcium has been leached from C2S and C3S phases by ammonium chloride solution. The SEM results are consistent with the XRD analysis.…”
Section: Calcium Leaching By Nh4cl With Conventional and Microwave Lementioning
confidence: 99%
“…The enrichment mechanism of phosphorus in steelmaking slag has been widely studied, [3][4][5][6] which indicated that phosphorus mainly enriched in dicalcium silicate phase in the form of solid solution as P-concentrating phase. According to these investigations, many researches on enhancing the phosphorus solubility in the P-concentrating phase have been carried out by modifying steelmaking slag with different additives such as Al 2 O 3 , 7,8) SiO 2 , 9) CaF 2 , 10) and TiO 2 .…”
Section: Introductionmentioning
confidence: 99%